Optimalisasi Motivasi Kerja Untuk Warga Taman Tuna Netra Yayasan Raudlatul Makfufin - Sevty Wahiddirani Saputri; Anis Syamsu Rizal; Heri Iswanto (Abdimisi, 2022)
The problem of blind people is a very complex problem, the presence of physical limitations of course creates problems, there are still many blind people who are unable to adapt to their environment, so that the impact on the functioning of the blind is not achieved properly. The community service entitled Optimizing Work Motivation for the Blind Taman Raudlatul Makfufin Buaran Serpong Foundation aims to prepare members of the Raudlatul Makfufin Foundation in Buaran Serpong so that they are ready and able to independently play an active role in carrying out daily activities, especially in their work, where internal conditions that is motivation. Work motivation in the context of this dedication is as a driving force for blind people to mobilize abilities, expertise, and skills so that they can carry out organizational goals in an effort to fulfill their individual needs. The results of this Community Service prove that the residents of the Raudlatul Makfufin Foundation in Buaran Serpong are able to carry out activities properly and carry out work routinely, so that work goals are achieved as expected.